2018
DOI: 10.1016/j.jbi.2018.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Semantic relation extraction aware of N-gram features from unstructured biomedical text

Abstract: Semantic relation extraction is a crucial step of automatically constructing a knowledge graph from unstructured biomedical text. Many real-world applications can benefit from it. As unsupervised relation extraction approaches, generative probabilistic models, Rel-LDA and Type-LDA, are receiving more attention in recent years. However, these two models inherit the bag-of-word assumption of the standard LDA model, which disable the exploitation of more distinguishable n-gram features. To overcome this limitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Xu et al [42] merged the idea of learning-to-rank into the textual information retrieval for query expansion. Wang et al [40] proposed Rel-TNG and Type-TNG models, which were combined with Rel-LDA and Type-LDA for semantic relation retrieval from biomedical documents. In deep learning-based methods, the basic ideas include transformer [10], Convolutional Neural Networks (CNN) [23], transfer learning [23][29], Graph Convolutional Network [39] and so on.…”
Section: B Biomedical Text Information Retrievalmentioning
confidence: 99%
“…Xu et al [42] merged the idea of learning-to-rank into the textual information retrieval for query expansion. Wang et al [40] proposed Rel-TNG and Type-TNG models, which were combined with Rel-LDA and Type-LDA for semantic relation retrieval from biomedical documents. In deep learning-based methods, the basic ideas include transformer [10], Convolutional Neural Networks (CNN) [23], transfer learning [23][29], Graph Convolutional Network [39] and so on.…”
Section: B Biomedical Text Information Retrievalmentioning
confidence: 99%
“…The model does not rely on hand-crafted or external natural language processing tools, such as parts-of-speech (POS) tagger, dependency parsers, etc. Extracting semantic relation from text has been performed by a group of researchers in [15]. Two models named Rel-TNG and Type-TNG were proposed that used topic n-Grams (TNG).…”
Section: Entity-relation Extractionmentioning
confidence: 99%
“…For instance, it was found that some key phrases may not be present in the abstract. Multi-word phrases within the text to extend the standard bag-of-words (BoW) approach are identified in [21] by generative probabilistic models. The multi-word phrases are then used to construct knowledge graphs representing the document.…”
Section: Text Mining Of Biomedical Documentsmentioning
confidence: 99%